2006
DOI: 10.1002/ajmg.b.30387
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of preproghrelin gene polymorphisms in susceptibility to bulimia nervosa

Abstract: Previous investigations have suggested that ghrelin, an endogenous orexigenic peptide, is involved in the pathology of eating disorders. We conducted a study to determine whether any preproghrelin gene polymorphisms are associated with eating disorders. Three hundred thirty-six eating disorder patients, including 131 anorexia nervosa (AN)-restricting types (AN-R), 97 AN-binge eating/purging types (AN-BP) and 108 bulimia nervosa (BN)-purging types (BN-P), and 300 healthy control subjects participated in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 31 publications
(32 reference statements)
4
34
2
3
Order By: Relevance
“…It must be noted, that the study of such genetic locus among Ukrainians was not carried out, and we first inform about the frequencies of alleles of р. [30,31]. The frequency of Met72 allele in our sample is 21 %, a bit higher than the data, given by НарМар (15,6 %, N = 90).…”
Section: Discussioncontrasting
confidence: 77%
“…It must be noted, that the study of such genetic locus among Ukrainians was not carried out, and we first inform about the frequencies of alleles of р. [30,31]. The frequency of Met72 allele in our sample is 21 %, a bit higher than the data, given by НарМар (15,6 %, N = 90).…”
Section: Discussioncontrasting
confidence: 77%
“…Moreover, different pro-ghrelin gene polymorphisms have been linked to obesity, and to bulimia nervosa purging individuals (Ando et al 2006;Gueorguiev et al 2002;Korbonits et al 2002;Ukkola et al 2001;Vivenza et al 2004;Vartiainen et al 2006) as well as methamphetamine withdrawal .…”
Section: The Central Ghrelin Signalling System Is Required For Rewardmentioning
confidence: 99%
“…It is noticeable that the studies were still inconclusive when the GHRL gene is investigated, these studies show different positive and negative associations with different EDs diagnoses 73,81,82,84,86 . However, when they analyzed the genes of the GHS-R and of the GOAT some studies have found a positive association between polymorphisms and the EDs 79 .…”
Section: C60t Asp20asp Rs2232165mentioning
confidence: 99%